Airway clearance treatments in bronchiectasis: feasibility of linking survey results to registry data and a survey of patients' and physiotherapists' practices. Issue 2 (20th March 2023) - McLeese, Rebecca H.; O'Neill, Katherine; O'Neill, Brenda; Chalmers, James D.; Boyd, Jeanette; De Soyza, Anthony; McChrystal, Ryan; Crichton, Megan L.; Bradley, Judy M.
Background and objective: There are limited data on airway clearance treatment (ACT) practices. This study aimed to: 1) assess the feasibility of collecting online surveys on ACTs from patients and physiotherapists and linking the patient survey data to outcome data in the Bronch-UK/EMBARC Registry; 2) assess the association between ACT practices and outcome data; and 3) ascertain the factors affecting physiotherapist ACT practices. Methods: Survey methodology was used to collect data from patients with bronchiectasis and physiotherapists in Northern Ireland. Associations between patient survey data and linked Bronch-UK/EMBARC Registry patient outcome data were explored. Results: It was feasible to conduct an online survey with patients with bronchiectasis and link the data to the Bronch-UK/EMBARC Registry. 13% of patients did not perform ACTs. ACTs were used more often by patients who were symptomatic/had more severe disease compared to those with milder symptoms/disease. Patients used ACTs when they were symptomatic rather than as a preventative management strategy. Physiotherapists generally followed the bronchiectasis guidelines, using the stepwise approach to management. Conclusion: Our survey provided information about the feasibility of linking online survey and patient registry data. This study provides up-to-date information on ACT practice throughout the course of the disease trajectory as well as insight into the implementation of bronchiectasis guidelines by physiotherapists. Future work should explore how to optimise ACT data collection to maximise the use of real-world ACT data in bronchiectasis research and inform priority ACT research questions. This study provides up-to-date information on ACT practice and implementation of bronchiectasis guidelines by physiotherapists. Future work should explore how to optimise ACT data collection to maximise use of real-world ACT data in bronchiectasis research. https://bit.ly/3AX90hQ